Heteroatom-containing thermosetting polyarylether resin as well as prepreg and halogen-free flame-retardant high-frequency high-speed copper-clad plate prepared from heteroatom-containing thermosetting polyarylether resin
By using a continuous flow microchannel reactor and maleic anhydride graft reaction in the thermoset polyaryl ether resin, a resin with excellent dielectric properties was prepared, which solved the problem of insufficient dielectric properties in the field of high-frequency and high-speed communication in traditional methods. , realizes low-cost industrial production of halogen-free flame retardant high-frequency high-speed copper clad plate.
Patent Information
- Application Number
- CN202411623427.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-07
AI Technical Summary
The existing thermoset copper clad plate has insufficient dielectric performance in the field of high-frequency and high-speed communications, and the traditional method has high production cost and complex processes, making it difficult to achieve industrial production of halogen-free flame-retardant high-frequency/high-speed copper clad plates.
A continuous flow microchannel reactor is used to prepare a thermoset polyarylether resin containing heteroatoms. By reacting maleic anhydride with an organometallic compound, the graft rate of unsaturated hydrocarbons is controlled to form a resin with excellent dielectric properties, and Semi-cured sheets are made by impregnating fiber cloth and baking, and are ultimately used to make high-frequency high-speed copper clad plates.
It realizes low-cost, easy to mass-produce halogen-free flame-retardant high-frequency high-speed copper clad plate, with excellent dielectric properties, mechanical strength and low thermal expansion coefficient, and is suitable for the manufacturing of multi-layer copper clad plates.
Smart Images

Figure CN119264343A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of communication materials, and in particular relates to a thermosetting polyarylether resin containing heteroatoms and a prepreg and a halogen-free flame-retardant high-frequency and high-speed copper-clad laminate prepared therefrom. Background Art
[0002] Copper clad laminates are widely used in mobile phones, computers, wearable devices, communication base stations, satellites, driverless cars, drones and intelligent robots, and are one of the key materials in the electronic communications and information industries. Traditional thermosetting resins represented by epoxy resins, phenolic resins and cyanate resins have high thermo-mechanical properties, low thermal expansion coefficients, good quality and low price, easy processing, and strong versatility. They are commonly used materials for making copper clad laminate substrates. After continuous exploration and optimization of formulas and processes, researchers have prepared various types of thermosetting copper clad laminates with qualified comprehensive performance, which meet the basic requirements of copper clad laminates in various segments of the electronic communications industry. However, the dielectric constant and dielectric loss of the above-mentioned traditional thermosetting copper clad laminates are generally very high, which means that they can only be used at low frequencies, and can no longer meet the higher performance requirements for substrate materials in the current high-frequency and high-speed communication fields.
[0003] Later, people developed thermosetting polyphenylene ether-based copper-clad laminates with excellent dielectric properties. At present, thermosetting polyphenylene ether resins can be divided into two categories: end vinyl modified and side vinyl modified. End vinyl modified polyphenylene ether has been commercialized, but its price is extremely expensive, and its cross-linking curing degree is not as good as that of side vinyl modified polyphenylene ether. Side vinyl modified polyphenylene ether has more abundant double bonds and can be self-cured, even without the addition of initiators. Wang Yaoxian et al. first halogenated polyphenylene ether and then used the reaction between halogenated polyphenylene ether and allyl Grignard reagent to prepare thermosetting polyphenylene ether resin with allyl modified side chain (Paper of the 13th National Composite Materials Academic Conference, 2004, 401-405; Chinese Patent CN1563145A; Polymer Bulletin, 2007, 59, 391-402.). However, there is no commercial mass production of allyl Grignard reagents, which often need to be made in the laboratory, and the preparation process is cumbersome, the production cost is high, and it is difficult to store and use. US Patents US3281393, US3422062, US20080194724A1 and Zhang Yufang et al. (Synthesis and Characterization of Cross-linkable Polyphenylene Ether, 2007, Master's Thesis) use phenol derivatives with double bonds such as 2,6-dimethylphenol and 2-allyl-6-methyl-phenol as monomers, potassium ferrocyanide or oxygen as oxidants, and prepare thermosetting polyphenylene ether resins with side allyl groups through oxidative condensation copolymerization. US3281393 further oxidizes the side allyl groups into epoxy functional groups. Similarly, there are no mass-produced products for double-bond phenol monomers represented by 2-allyl-6-methyl-phenol, and the industrial mass production of thermosetting polyphenylene ether cannot be achieved through this copolymerization method. US Patents US3522326, US4923932 and US5218030 use organic metal compounds such as butyl lithium to metallize polyphenylene ether first, and then react with halogenated unsaturated hydrocarbons to graft unsaturated bonds onto the main chain of polyphenylene ether. US3522326 also uses a similar method to modify ethylene oxide onto the polyphenylene ether chain to prepare a thermosetting polyphenylene ether resin that can be cured with epoxy resin. Although organic metal compounds such as butyl lithium have commercial products, they are highly reactive. In traditional kettle reactors, their reactions are highly exothermic, the process is difficult to control, and the risk is high. In addition, it is necessary to ensure that the entire reaction process is always in an inert atmosphere, which places extremely high demands on reaction equipment and process control.
[0004] In addition, due to increasingly stringent environmental laws and policies, the demand for halogen-free flame-retardant high-frequency / high-speed copper clad laminates has also shown a clear upward trend recently. Introducing heteroatoms into the molecular chain of polyarylether resin to improve its flame retardant properties is a good way to achieve halogen-free flame retardancy for high-frequency / high-speed copper clad laminates.
[0005] The continuous flow microchannel reactor is a small reaction system with a pipeline size much smaller than that of a conventional reactor. The miniaturization of the reaction channel can significantly increase the contact area between the channel and the heat exchange medium, improve the heat exchange efficiency, and effectively handle the heat released when polyarylether reacts with organometallic compounds, ensuring that the reaction is orderly, controllable and safe. The extremely strong turbulent process in the microchannel can also increase the mass transfer effect exponentially. At present, the continuous flow microchannel reactor is mainly used in the synthesis of small molecules and their industrial production. There are not many studies and reports on its industrial synthesis and modification of polymers, and most of them are only in the laboratory stage. So far, there has been no research report on the preparation of thermosetting polyarylether using a continuous flow microchannel reactor. In addition, the continuous flow microchannel reactor can realize multi-step continuous reaction, and can be directly scaled up to achieve mass production without pilot testing. It has high safety, controllable production process and high reaction selectivity. Summary of the invention
[0006] The purpose of the present invention is to provide a thermosetting polyarylether resin containing heteroatoms and a prepreg and a halogen-free flame-retardant high-frequency and high-speed copper-clad laminate prepared therefrom. In the present invention, the grafting site of the unsaturated hydrocarbon can be the Ar-H site or -CH3 on the polyarylether benzene ring; the grafting rate of the unsaturated hydrocarbon on the polyarylether molecular chain refers to the proportion of the repeating units grafted with the unsaturated hydrocarbon in the polyarylether molecular chain to all the repeating units in the polyarylether molecular chain; the grafting rate can be controlled by the molar ratio of the organometallic compound to the repeating units in the polyarylether molecular chain, or / and the molar ratio of the unsaturated hydrocarbon containing heteroatoms to the organometallic compound.
[0007] The present invention further utilizes the uniform dispersion of the composition prepared by the thermosetting polyarylether resin containing heteroatoms, and obtains a prepreg with uniform glue content, strong resin adhesion, flat surface, suitable toughness and viscosity through the steps of impregnating fiber cloth and baking. Finally, the thermosetting copper clad laminate made of the prepreg, film and copper foil has excellent dielectric properties, high mechanical strength, low thermal expansion coefficient, high copper foil peeling strength, good uniformity of various properties, can achieve halogen-free flame retardancy, and can be used to make multi-layer copper clad laminates.
[0008] The present application provides a thermosetting polyarylether resin containing heteroatoms, including 5.0 wt / v% polyphenylene ether / THF solution, 0.5 mol / L n-butyl lithium / n-hexane solution, 1.5 mol / L maleic anhydride / THF solution, methanol, toluene and allyl mercaptan.
[0009] The preparation method of the thermosetting polyarylether resin containing heteroatoms comprises the following steps in sequence:
[0010] S1, respectively passing an organic solution of polyarylether and an organic solution of an organometallic compound into a direct-flow microchannel reactor for preheating through a metering pump; subsequently, the preheated organic solution of polyarylether and the organic solution of an organometallic compound are simultaneously pumped into a reaction module A consisting of N enhanced mixed continuous flow microchannel reactors for reaction; then, the product solution A flowing out of the reaction module A and the organic solution of maleic anhydride are synchronously pumped into a reaction module B consisting of M enhanced mixed continuous flow microchannel reactors for reaction, and then the product solution B flowing out of the reaction module B is added to a poor solvent for polyarylether, stirred evenly, and allowed to stand for the product to be fully precipitated and settled, and then filtered, washed and dried to obtain a polyarylether resin grafted with maleic anhydride;
[0011] S2. Re-dissolving the maleic anhydride grafted polyarylether resin in an organic solvent, adding an unsaturated hydrocarbon containing heteroatoms, and stirring the mixture at 0-130° C. for 2-96 hours to obtain an organic solution of a thermosetting polyarylether resin containing heteroatoms.
[0012] Optionally, the polyarylether in step S1 refers to a mixture of one or more of the polymers having the following chemical structures in the molecular chain:
[0013]
[0014] Wherein, a is between 8 and 400; b≥1, c≥1, and b+c is between 9 and 400; d≥1, e≥1, and d+e is between 9 and 400; f≥0, g≥1, h≥1, i≥1, and g+h+i is between 10 and 400; j≥1, k≥1, l≥1, and j+k+l is between 10 and 400; m≥1, n≥1, o≥1, p≥1, and m+n+o+p is between 11 and 400;
[0015] Wherein, R1 and R2 are a combination of the following functional groups:
[0016]
[0017] wherein R3, R4, R5, R6, R7, R8, R9, R10 and R11 each independently represent H and a C1-C12 hydrocarbon chain;
[0018] In addition, one or a mixture of C1-C12 hydrocarbon chains, aromatic groups and their derivatives may be grafted onto the 3rd and 4th positions of the benzene ring in the repeating unit of the polyarylether molecular chain;
[0019] The concentration of the organic solution of polyarylether is 0.01-25wt%; the flux of the organic solution of polyarylether in the direct-flow microchannel reactor is controlled at 1-40mL / min.
[0020] Optionally, the organometallic compound in step S1 is one of alkyl lithium, alkyl sodium and alkyl potassium, or a mixture of several of them; the concentration of the organic solution of the organometallic compound is 0.05-3 mol / L; the solvent in the organic solution of the organometallic compound is one of ether solvents that do not react with the organometallic compound and maleic anhydride, or a mixture of one or several composite solvents of hydrocarbon organic solvents and ditertiary amines, the hydrocarbon organic solvents include cyclohexane, n-hexane, benzene, toluene and xylene, the ditertiary amines include tetramethylethylenediamine, and the ditertiary amines account for 0.2-10wt% of the hydrocarbon organic solvents; the water content of the organic solution of the organometallic compound is ≤0.1wt%, and the oxygen content is ≤0.1v / wt%.
[0021] The molar ratio between the repeating unit and the organometallic compound in the molecular chain of the polyarylether is 1:0.0001-1:2.001;
[0022] The molar ratio between the maleic anhydride and the organometallic compound is 0.01:1-1.01:1.
[0023] Optionally, the direct flow microchannel in step S1 is a channel of a tubular structure, the preheating residence time is set to 5-300s, and the preheating temperature is set to -78°C-150°C; the preheating is controlled by an external heat exchanger, and the heat exchange medium in the external heat exchanger is one of heat transfer oil, water, ice water, ice brine and ethanol;
[0024] The reaction temperature in the reaction modules A and B is also controlled by an external heat exchanger and is consistent with the preheating temperature, the N is between 1-20, the M is between 1-20, the channel in the enhanced hybrid continuous flow microchannel reactor is one of a heart-shaped structure, a water drop-shaped structure, a T-shaped structure, a spherical structure and a spherical structure with baffles, or a combination of several of them, the total reaction time of the polyarylether and the organometallic compound in the reaction module A is 1s-3000s, and the total reaction time of the product solution A and maleic anhydride in the reaction module B is 1s-3000s;
[0025] The hydraulic diameter of the channel in the microchannel reactor is 0.25-10.0 mm, and its material is one of glass, metal and its alloy, ceramic, single crystal silicon, glass with an anti-corrosion layer on the surface, metal and its alloy with an anti-corrosion layer on the surface, ceramic with an anti-corrosion layer on the surface, single crystal silicon with an anti-corrosion layer on the surface, fluorine-containing resin and highly cross-linked thermosetting resin.
[0026] Optionally, the poor solvent for the polyarylene ether in step S1 is one or a mixture of methanol, ethanol, isopropanol, butanol, ether and ester.
[0027] Optionally, the hydroxylated unsaturated hydrocarbon in step S2 is one or a mixture of substances having the following chemical structures:
[0028]
[0029] Wherein, X1 represents one of -SH, -NH, -NH2, -PH, R12 is not limited, R13, R14 and R15 each independently represent H, methyl and ethyl; the molar ratio of the unsaturated hydrocarbon containing heteroatoms to maleic anhydride is controlled in the range of 0.1:1-1.001:1.
[0030] A prepreg prepared from a thermosetting polyarylether resin containing heteroatoms, the preparation method comprising: adding a polydiene resin, a bismaleimide resin, a crosslinking agent and an initiator to an organic solution of the thermosetting polyarylether resin containing heteroatoms, stirring evenly to obtain a uniform dispersion of a thermosetting polyarylether resin-based composition containing heteroatoms, wherein the solid content of the dispersion is controlled to be 20-80wt / v%; then impregnating a fiber cloth with the uniform dispersion of the thermosetting polyarylether resin-based composition containing heteroatoms, and baking and drying to obtain the prepreg.
[0031] A high-frequency copper-clad laminate prepared from a prepreg, the preparation method comprising: laminating the prepreg and the copper foil covering the surface together, and preparing the halogen-free flame-retardant high-frequency and high-speed copper-clad laminate through a lamination process.
[0032] Optionally, the number average molecular weight of the polydiene resin is between 500 and 20,000, and the side groups of a single polydiene polymer chain contain at least 3 reactive carbon-carbon double bonds in total;
[0033] The crosslinking agent is one or a mixture of TAIC (triallyl isocyanurate), TAC (triallyl cyanurate), divinylbenzene, trimethylolpropane trimethacrylate, bismaleimide and derivatives thereof, and its amount accounts for 0-30.0wt% of the heteroatom-containing thermosetting polyarylether resin-based composition;
[0034] The initiator is one or a mixture of free radical initiators such as peroxides, azo compounds and redox systems that can be dissolved in a solvent that allows the heteroatom-containing thermosetting polyarylether resin-based composition to be uniformly dispersed, and the amount used is 0.01-5wt% of the heteroatom-containing thermosetting polyarylether resin-based composition;
[0035] The solvent of the uniform dispersion is one of water and an organic solvent, or a mixture of several solvents that can disperse the thermosetting polyarylether resin-based composition containing heteroatoms;
[0036] When the polydiene resin, crosslinking agent and initiator are added, fillers, flame retardants, compatibilizers, toughening agents and modified resins may also be added.
[0037] Optionally, the high-frequency copper clad laminate also includes a film, which is a mixture of one or more of fluoropolymers, polyimides, polyolefins, polyaromatic hydrocarbons, polyamides, polyether ketones, polyetherether ketones, polyarylethers, polyarylether sulfides, polyarylether sulfones, polyarylether sulfones, polyarylether ketones, polyarylether sulfide ketones, polyethersulfoneketones, polyarylether sulfone nitrile, polyarylether sulfone nitrile, polyphenylquinoxaline, phenolic resins, epoxy resins, cyanate resins, polyesters, polycarbonates, polyurethanes and polyoxymethylene and their derivatives.
[0038] Compared with the prior art, the technical solution of this application has the following beneficial effects:
[0039] The invention has mild preparation conditions, low production cost, is easy to mass-produce and scale production, has strong universality, and has a good industrial production foundation and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0041] Figure 1 The present invention is a thermosetting polyarylether resin containing heteroatoms, a prepreg prepared therefrom, and a halogen-free flame-retardant high-frequency and high-speed copper-clad laminate of Examples 1-6. DETAILED DESCRIPTION
[0042] Synthesis example 1
[0043] A 5.0 wt / v% polyphenylene ether / THF solution and a 0.5 mol / L n-butyl lithium / n-hexane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.07; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the preheating residence time was set to 30 s. The preheating temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added, and the molar ratio of allyl mercaptan to maleic anhydride is controlled to be 1:1. After stirring and reacting at 60°C for 48h, a thermosetting polyarylether resin / toluene solution containing heteroatoms is obtained. The 1H-NMR test shows that the side vinyl grafting rate of the product is 4.15wt%.
[0044] Synthesis example 2
[0045] A 5.0 wt / v% polyphenylene ether / THF solution and a 0.5 mol / L n-butyl lithium / n-hexane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.12; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the preheating residence time was set to 30 s. The preheating temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added, and the molar ratio of allyl mercaptan to maleic anhydride is controlled to be 1:1. After stirring and reacting at 60°C for 48h, a thermosetting polyarylether resin / toluene solution containing heteroatoms is obtained. The 1H-NMR test shows that the side vinyl grafting rate of the product is 9.23wt%.
[0046] 0.5 wt% dicumyl peroxide was added to the thermosetting polyarylether resin / toluene solution collected in Synthesis Example 2, and after being stirred evenly, the solution was placed in a 45°C blowing oven for heat treatment to fully evaporate the solvent to obtain a polymer film; finally, the polymer film was placed in a 180°C oven for heat treatment for 30 minutes to obtain a cross-linked polyphenylene ether film. Even when heated by toluene, the cross-linked polyphenylene ether film could no longer be dissolved in toluene.
[0047] Synthesis example 3
[0048] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.2 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.28; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the reaction residence time was 200 s. The temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and vinyl aniline is added to control the molar ratio of vinyl aniline to maleic anhydride to be 0.51:1, and after stirring and reacting at 50°C for 48h, a thermosetting polyarylether resin / toluene solution containing heteroatoms is obtained. The 1H-NMR test shows that the side vinyl grafting rate of the product is 12.3wt%.
[0049] Synthesis example 4
[0050] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.6 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.38; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the preheating residence time was set to 30 s. The temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 0.95:1, and after stirring the reaction at 60°C for 72h, a thermosetting polyarylether resin / toluene solution containing heteroatoms is obtained. The 1H-NMR test shows that the side vinyl grafting rate of the product is 28.1wt%.
[0051] Synthesis example 5
[0052] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.6 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.35; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating was set to The temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 1:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added, and the molar ratio of allyl mercaptan to maleic anhydride is controlled to be 0.85:1. After stirring and reacting at 60°C for 72h, a thermosetting polyarylether resin / toluene solution containing heteroatoms is obtained. The 1H-NMR test shows that the side vinyl grafting rate of the product is 23.3wt%.
[0053] Synthesis example 6
[0054] A 5.0 wt / v% polyphenylene ether / THF solution and a 1.2 mol / L tert-butyl lithium / n-pentane solution were respectively pumped into the straight channel module of the Corning high-throughput microchannel reactor for preheating by a metering pump, and the preheating temperature was set to 5°C and the preheating residence time was 30 s. The molar ratio between the repeating unit in the polyarylether molecular chain and the n-butyl lithium was controlled at 1:0.26; the preheated 5.0 wt / v% polyphenylene ether / THF solution and the 1.6 mol / L n-butyl lithium / n-hexane solution were directly connected to the reaction module A composed of 4 heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, and the reaction temperature was also controlled at 5°C and the reaction residence time was 200 s; similarly, a 1.5 mol / L maleic anhydride / THF solution was pumped into the straight channel module of the Corning high-throughput microchannel reactor by a metering pump for preheating, and the preheating temperature was set to 5°C and the preheating residence time was set to 30 s. The temperature is 5°C and the preheating residence time is 30s; the product solution flowing out of the reaction module A and the preheated maleic anhydride / THF solution are injected into the reaction module B composed of three heart-shaped channel modules of the Corning high-throughput microchannel reactor for mixed reaction, the molar ratio between maleic anhydride and n-butyl lithium is controlled to be 0.98:1, the reaction temperature is controlled at 25°C, and the reaction residence time is 160s; the product solution flowing out of the reaction module B is collected, and excess methanol is added to make the polymer fully precipitate and precipitate, and then filtered, washed with methanol and dried to obtain maleic anhydride grafted polyphenylene ether resin; the maleic anhydride grafted polyphenylene ether resin is redissolved in toluene, and allyl mercaptan is added to control the molar ratio of allyl mercaptan to maleic anhydride to be 1:1, and after stirring the reaction at 60°C for 72h, a thermosetting polyarylether resin / toluene solution containing heteroatoms is obtained. The 1H-NMR test shows that the side vinyl grafting rate of the product is 19.5wt%.
[0055] Example 1
[0056] Take 100 parts of the thermosetting polyarylether resin containing heteroatoms in Synthesis Example 1, 35 parts of polybutadiene (Crayville Ricon 154), 5 parts of TAIC, 10 parts of bismaleimide resin, 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ricon 130MA8), 50 parts of silicon oxide, 200 parts of boehmite, 10 parts of aluminum oxide, 50 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50 ° C for 24 hours, fully dissolve and disperse uniformly; reduce Bring to room temperature, add 3.5 parts of dibenzoyl peroxide, and stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5 minutes, and the second stage baking temperature is 120°C, the time is 2 minutes; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0057] Example 2
[0058] Take 100 parts of the thermosetting polyarylether resin containing heteroatoms in Synthesis Example 2, 30 parts of polybutadiene (Crayville Ricon 154), 10 parts of bismaleimide resin, 5 parts of divinylbenzene, 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ricon 130MA8), 100 parts of silicon oxide, 150 parts of boehmite, 10 parts of aluminum oxide, 40 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50 ° C for 24 hours, fully dissolve and disperse uniformly; reduce Bring to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5 minutes, and the second stage baking temperature is 120°C, the time is 2 minutes; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0059] Example 3
[0060] Take 100 parts of the thermosetting polyarylether resin containing heteroatoms in Synthesis Example 3, 5 parts of divinylbenzene, 10 parts of bismaleimide resin, 30 parts of polybutadiene (Crayville Ricon 154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ricon 130MA8), 120 parts of silicon oxide, 130 parts of boehmite, 10 parts of aluminum oxide, 35 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50 ° C for 24 hours, fully dissolve and disperse uniformly; reduce Bring to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5 minutes, and the second stage baking temperature is 120°C, the time is 2 minutes; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0061] Example 4
[0062] Take 100 parts of the thermosetting polyarylether resin containing heteroatoms in Synthesis Example 4, 5 parts of trimethylolpropane trimethacrylate, 10 parts of bismaleimide resin, 28 parts of polybutadiene (Crayville Ricon 154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ricon 130MA8), 150 parts of silicon oxide, 100 parts of boehmite, 10 parts of aluminum oxide, 35 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50 ° C for 24 hours, and fully dissolve and disperse uniform; cool to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90℃, the time is 5min, and the second stage baking temperature is 120℃, the time is 2min; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides respectively, and laminate for 4h at a pressure of 45-75kg / cm2 and a temperature of 220℃ to obtain a copper clad laminate.
[0063] Example 5
[0064] Take 100 parts of the thermosetting polyarylether resin containing heteroatoms in Synthesis Example 5, 5 parts of TAIC, 15 parts of bismaleimide resin, 25 parts of polybutadiene (Crayville Ricon 154), 5 parts of polybutadiene-maleic anhydride copolymer (Crayville Ricon 130MA8), 150 parts of silicon oxide, 100 parts of boehmite, 10 parts of aluminum oxide, 30 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50 ° C for 24 hours, fully dissolve and disperse uniformly; reduce Bring to room temperature, add 3.5 parts of dibenzoyl peroxide, and further stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5 minutes, and the second stage baking temperature is 120°C, the time is 2 minutes; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
[0065] Example 6
[0066] Take 100 parts of the thermosetting polyarylether resin containing heteroatoms in Synthesis Example 6, 8 parts of bismaleimide resin, 7 parts of divinylbenzene, 20 parts of polybutadiene (Cray Valley Ricon 154), 5 parts of polybutadiene-maleic anhydride copolymer (Cray Valley Ricon 130MA8), 175 parts of silicon oxide, 75 parts of boehmite, 10 parts of aluminum oxide, 30 parts of hexaphenoxy cyclotriphosphazene and 550 parts of toluene, stir at 50 ° C for 24 hours, fully dissolve and disperse evenly; reduce to At room temperature, add 3.5 parts of dibenzoyl peroxide and stir evenly; use 1078 glass fiber cloth to dip glue, and then bake and dry to obtain a semi-cured sheet, wherein the first stage baking temperature is 90°C, the time is 5 minutes, and the second stage baking temperature is 120°C, the time is 2 minutes; take 9 semi-cured sheets and stack them together, attach loz copper foil on both sides, and laminate for 4 hours at a pressure of 45-75kg / cm2 and a temperature of 220°C to obtain a copper clad laminate.
Claims
1. A thermosetting polyarylether resin containing heteroatoms, characterized in that: The invention comprises a 5.0 wt / v% polyphenylene ether / THF solution, a 0.5 mol / L n-butyl lithium / n-hexane solution, a 1.5 mol / L maleic anhydride / THF solution, methanol, toluene and allyl mercaptan, The preparation method of the thermosetting polyarylether resin containing heteroatoms comprises the following steps in sequence: S1, respectively passing an organic solution of polyarylether and an organic solution of an organometallic compound into a direct-flow microchannel reactor for preheating through a metering pump; subsequently, the preheated organic solution of polyarylether and the organic solution of an organometallic compound are simultaneously pumped into a reaction module A consisting of N enhanced mixed continuous flow microchannel reactors for reaction; then, the product solution A flowing out of the reaction module A and the organic solution of maleic anhydride are synchronously pumped into a reaction module B consisting of M enhanced mixed continuous flow microchannel reactors for reaction, and then the product solution B flowing out of the reaction module B is added to a poor solvent for polyarylether, stirred evenly, and allowed to stand for the product to be fully precipitated and settled, and then filtered, washed and dried to obtain a polyarylether resin grafted with maleic anhydride; S2. Re-dissolving the maleic anhydride grafted polyarylether resin in an organic solvent, adding an unsaturated hydrocarbon containing heteroatoms, and stirring the mixture at 0-130° C. for 2-96 hours to obtain an organic solution of a thermosetting polyarylether resin containing heteroatoms.
2. The thermosetting polyarylether resin containing heteroatoms according to claim 1, characterized in that: The polyarylether in step S1 refers to a mixture of one or more of the polymers having the following chemical structures in the molecular chain: Wherein, a is between 8 and 400; b≥1, c≥1, and b+c is between 9 and 400; d≥1, e≥1, and d+e is between 9 and 400; f≥0, g≥1, h≥1, i≥1, and g+h+i is between 10 and 400; j≥1, k≥1, l≥1, and j+k+l is between 10 and 400; m≥1, n≥1, o≥1, p≥1, and m+n+o+p is between 11 and 400; Wherein, R1 and R2 are a combination of the following functional groups: wherein R3, R4, R5, R6, R7, R8, R9, R10 and R11 each independently represent H and a C1-C12 hydrocarbon chain; In addition, one or a mixture of C1-C12 hydrocarbon chains, aromatic groups and their derivatives may be grafted onto the 3rd and 4th positions of the benzene ring in the repeating unit of the polyarylether molecular chain; The concentration of the organic solution of polyarylether is 0.01-25wt%; the flux of the organic solution of polyarylether in the direct-flow microchannel reactor is controlled at 1-40mL / min.
3. The method for preparing a thermosetting polyarylether resin containing heteroatoms according to claim 1, characterized in that: The organometallic compound in step S1 is one of alkyl lithium, alkyl sodium and alkyl potassium, or a mixture of several thereof; the concentration of the organic solution of the organometallic compound is 0.05-3 mol / L; the solvent in the organic solution of the organometallic compound is one of ether solvents that do not react with the organometallic compound and maleic anhydride, or a mixture of one or several composite solvents of hydrocarbon organic solvents and di-tertiary amine, the hydrocarbon organic solvent includes cyclohexane, n-hexane, benzene, toluene and xylene, the di-tertiary amine includes tetramethylethylenediamine, and the di-tertiary amine accounts for 0.2-10wt% of the hydrocarbon organic solvent; the water content of the organic solution of the organometallic compound is ≤0.1wt%, and the oxygen content is ≤0.1v / wt%. The molar ratio between the repeating unit and the organometallic compound in the molecular chain of the polyarylether is 1:0.0001-1:2.001; The molar ratio between the maleic anhydride and the organometallic compound is 0.01:1-1.01:
1.
4. The thermosetting polyarylether resin containing heteroatoms according to claim 1, characterized in that: The direct-flow microchannel in step S1 is a channel of tubular structure, and the preheating residence time is set to 5-300s, and the preheating temperature is set to -78°C-150°C; the preheating is controlled by an external heat exchanger, and the heat exchange medium in the external heat exchanger is one of heat transfer oil, water, ice water, ice salt water and ethanol; The reaction temperature in the reaction modules A and B is also controlled by an external heat exchanger and is consistent with the preheating temperature, the N is between 1-20, the M is between 1-20, the channel in the enhanced hybrid continuous flow microchannel reactor is one of a heart-shaped structure, a water drop-shaped structure, a T-shaped structure, a spherical structure and a spherical structure with baffles, or a combination of several of them, the total reaction time of the polyarylether and the organometallic compound in the reaction module A is 1s-3000s, and the total reaction time of the product solution A and maleic anhydride in the reaction module B is 1s-3000s; The hydraulic diameter of the channel in the microchannel reactor is 0.25-10.0 mm, and its material is one of glass, metal and its alloy, ceramic, single crystal silicon, glass with an anti-corrosion layer on the surface, metal and its alloy with an anti-corrosion layer on the surface, ceramic with an anti-corrosion layer on the surface, single crystal silicon with an anti-corrosion layer on the surface, fluorine-containing resin and highly cross-linked thermosetting resin.
5. The thermosetting polyarylether resin containing heteroatoms according to claim 1, characterized in that: The poor solvent of the polyarylether in step S1 is one or a mixture of methanol, ethanol, isopropanol, butanol, ether and ester.
6. The thermosetting polyarylether resin containing heteroatoms according to claim 1, characterized in that: The hydroxylated unsaturated hydrocarbon in step S2 is one or a mixture of substances having the following chemical structures: Wherein, X1 represents one of -SH, -NH, -NH2, -PH, R12 is not limited, R13, R14 and R15 each independently represent H, methyl and ethyl; the molar ratio of the unsaturated hydrocarbon containing heteroatoms to maleic anhydride is controlled in the range of 0.1:1-1.001:
1.
7. A prepreg prepared from the thermosetting polyarylether resin containing heteroatoms as claimed in claim 1, characterized in that The preparation method comprises the following steps: adding polydiene resin, bismaleimide resin, crosslinking agent and initiator to an organic solution of the thermosetting polyarylether resin containing heteroatoms, stirring evenly to obtain a uniform dispersion of the thermosetting polyarylether resin-based composition containing heteroatoms, and controlling the solid content thereof to be 20-80wt / v%; then impregnating a fiber cloth with the uniform dispersion of the thermosetting polyarylether resin-based composition containing heteroatoms, and baking and drying to obtain the semi-cured sheet.
8. A high-frequency copper-clad laminate prepared from the prepreg according to claim 7, characterized in that The preparation method is: stacking the prepreg and the copper foil covering the surface together, and preparing the halogen-free flame-retardant high-frequency and high-speed copper-clad laminate through a lamination process.
9. The prepreg prepared from a thermosetting polyarylether resin containing heteroatoms according to claim 7, characterized in that:
7. The number average molecular weight of the polydiene resin is between 500 and 20,000, and the side groups of a single polydiene polymer chain contain at least 3 reactive carbon-carbon double bonds in total; The crosslinking agent is one or a mixture of TAIC (triallyl isocyanurate), TAC (triallyl cyanurate), divinylbenzene, trimethylolpropane trimethacrylate, bismaleimide and derivatives thereof, and its amount accounts for 0-30.0wt% of the heteroatom-containing thermosetting polyarylether resin-based composition; The initiator is one or a mixture of free radical initiators such as peroxides, azo compounds and redox systems that can be dissolved in a solvent that allows the heteroatom-containing thermosetting polyarylether resin-based composition to be uniformly dispersed, and the amount used is 0.01-5wt% of the heteroatom-containing thermosetting polyarylether resin-based composition; The solvent of the uniform dispersion is one of water and organic solvent, or a mixture of several solvents that can disperse the thermosetting polyarylether resin-based composition containing heteroatoms; When the polydiene resin, crosslinking agent and initiator are added, fillers, flame retardants, compatibilizers, toughening agents and modified resins may also be added.
10. The high-frequency copper-clad laminate prepared from a prepreg according to claim 8, characterized in that: The high-frequency copper clad laminate also includes a film, which is a mixture of one or more of fluorine-containing polymers, polyimides, polyolefins, polyaromatic hydrocarbons, polyamides, polyether ketones, polyether ether ketones, polyarylethers, polyarylether sulfides, polyarylether sulfones, polyarylether sulfones, polyarylether ketones, polyarylether sulfide ketones, polyether sulfone ketones, polyarylether sulfone nitrile, polyarylether sulfone nitrile, polyphenylquinoxaline, phenolic resins, epoxy resins, cyanate resins, polyesters, polycarbonates, polyurethanes, polyoxymethylenes and their derivatives.
Citation Information
Patent Citations
Preparing thermosetting phlyphenylether through Geliya reagent in polyphenylether halide and allyl group type
CN1563145A
Method of forming a crosslinked poly(arylene ether) film, and film formed thereby
US20080194724A1
Phenylene oxide polymers substituted with epoxidized alkenyl groups
US3281393A
Copolymers of alkenyl phenol
US3422062A
Graft copolymers of polyphenylene ethers
US3522326A
Cited By
Ultralow-electrical-property resin composition and prepreg and copper-clad plate thereof
CN121005841A